Comanche Society : Before the Reservation. - Betty, Gerald (Elma Dill Russell Spencer series in the West and Southwest ;, 2005)
Once called the Lords of the Plains, the Comanches were long portrayed as loose bands of marauding raiders who capitalized on the Spanish introduction of horses to raise their people out of primitive poverty through bison hunting and fierce warfare. In Comanche Society, Gerald Betty develops an exciting and sophisticated perspective on what he regards as the driving force of Comanche life: kinship. Betty details the kinship patterns that underlay all social organization and social behavior among the Comanches and uses the insights gained to explain the way Comanches lives and the manner in which they interacted with Europeans. Rather than a narrative history of the Comanches, this account presents analyses of the formation of clans and how they functioned across wide areas to produce cooperation and alliances: of hierarchy based in family and generational relationships; and of ancestor worship and related religious ceremonies as the basis for social solidarity. Betty then considers a number of aspects of Comanche life--pastoralism, migration and nomadism, economics and trade, warfare and violence--and how these developed along kinship lines. Betty describes in detail the Comanche horse culture as it was observed by the Spaniards and the Indian adaptation of Iberian practices. This cutting-edge history draws on original research in extensive primary documents providing an interpretive gaze into the culture of eighteenth--and nineteenth-century Comanche life.